COMPARATIVE ANALYSIS OF OPTICAL FLOW MEASUREMENT TECHNIQUE - NIZAM AKBAR, AMAR NAZMI ZULKARNAIN (IRC, 2017)
In 2010, an explosion occurred in the Macondo well in the Gulf of Mexico (GoM) that caused the oil rig to sink to the bottom of the ocean. At that time, there was no accurate method to estimate the flow rate of the hydrocarbon leakage. Timothy J. Crone used a noninvasive flow measurement technique, optical plume velocimetry to determine the flow rate using image analysis. There are several methods to estimate the flow rate measurement namely temporal cross correlation, frequency domain cross correlation, average square difference function, ASDF and average magnitude difference function, AMDF. The most important parameter in these methods is the time delay. However, Crone neglected the frequency domain cross correlation which may give a better flow rate estimation. The main motivation of this research is to do a comparative analysis of the four cross correlation algorithm as mentioned above. The four algorithms were used to estimate the flow rate where five simulations with five different flow rates were measured in order to determine the accuracy of each algorithm. Crone’s experimental setup was replicated and a DSLR camera was used to record the flow.